2002
DOI: 10.1046/j.1460-2695.2002.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Very high cycle regime fatigue of thin walled tubes made from austenitic stainless steel

Abstract: Fatigue life data of cold worked tubes (diameter 4 mm, wall thicknesses 0.25 and 0.30 mm) of an austenitic stainless steel, AISI 904 L, were measured in the regime ranging from 2 × 105 to 1010 cycles to failure. The influence of the loading frequency was investigated as data were obtained in conventional rotating bending at 160 and 200 Hz and in ultrasonic axial loading at 20 kHz. Above 5 × 106 cycles the fatigue lifetimes found with both methods were comparable. The results show that the slope of the S–N curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Fractographic observations. Fracture surface observations of the entire cross section showed that the crack initiated at the specimen surface for both materials as commonly observed for type I materials [2,[13][14]. For both materials, microcracks at grain boundaries between grains with and without persistent slip markings were highlighted ( Fig.…”
Section: Resultssupporting
confidence: 60%
“…Fractographic observations. Fracture surface observations of the entire cross section showed that the crack initiated at the specimen surface for both materials as commonly observed for type I materials [2,[13][14]. For both materials, microcracks at grain boundaries between grains with and without persistent slip markings were highlighted ( Fig.…”
Section: Resultssupporting
confidence: 60%
“…In the first regime, failure occurs between 3.6 Â 10 6 and (Fig. 4) showed that the crack initiated at the specimen surface as commonly observed for type I materials [8,14,16]. SEM investigations of the fracture surface and of the surface grains close to the fracture surface reveal that the roughness at the crack initiation zone is very low with regard to the rest of the fracture surface.…”
Section: S-n Curvementioning
confidence: 89%
“…Müller-Bollenhagen et al [9] showed for an annealed metastable austenitic stainless steel that failure does not occur beyond 2•10 6 cycles, provided the initial microstructure is fully austenitic. In case of stable austenitic stainless steels Takahashi and Ogawa [11] and Carstensen et al [12] found specimen fatigue failure beyond 10 7 and even 10 8 cycles. It should be mentioned that both steels were investigated in cold worked conditions.…”
Section: Introductionmentioning
confidence: 97%